Body sizes of hosts and parasitoids in individual feeding relationships. - Cohen, J; Jonsson, T; Müller, C; Godfray, H; Savage, V (2005)
In a natural community of 49 species (12 species of aphids and 37 species of their parasitoids), body lengths of 2,151 parasitoid individuals were, to an excellent approximation, related to the body lengths of their individual aphid hosts by a power law with an exponent close to 3/4. Two alternative models predict this exponent. One is based on surface area to volume relationships. The other is based on recent developments in metabolic ecology. Both models require a changing ratio (in both host and parasitoid) of length to diameter with increasing body length. These changing ratios are manifested differently in the two models and result in testably different predictions for the scaling of body form with increasing size. The estimated exponent of 3/4 for the relationship between individual host body size and individual parasitoid body size degrades to an exponent of nearly 1/2, and the scatter in the relationship between aphid and parasitoid body length is substantially increased, if the average length of a parasitoid species is examined as a function of the average length of its aphid host species instead of using measurements of individuals.